A Multi-Criteria Decision Support System for Prioritizing Forest and Land Rehabilitation Using MOORA and ORESTE - Yustria Handika Siregar; Mohammad Badri; Nora Asyiqin; Syafhira Ananda Galasca; Fathur Rahman (Ali Institute of Reseach and Publication, 2025)
This study integrates two analytical approaches, Multi-Objective Optimization by Ratio Analysis (MOORA) and Organization, Rangement Et Synthese De Donnes Relationnelles (ORESTE), to identify priority locations for forest and land rehabilitation in North Sumatra. The study evaluates six key criteria, including rehabilitation area size, carbon emissions, ecosystem degradation, biodiversity, rehabilitation potential, and environmental impact, across ten candidate sites. Initially, the MOORA method was applied to assess quantitative factors, revealing that the technical potential among the locations was nearly uniform. Subsequently, the ORESTE method was employed to evaluate qualitative factors, including community participation, socio-cultural values, and institutional support. This analysis revealed significant disparities in social readiness. For instance, South Tapanuli and Mandailing Natal emerged as top priorities due to their robust social support systems, while West Pakpak faced significant social challenges. This integrated approach offers a comprehensive framework that balances both technical and social dimensions for the successful implementation of sustainable forest rehabilitation programs.